The Effectiveness of Community Information Group Implementation in Community Empowerment: a study in Palembang City - Yanuar Luqman; Muhammad Bayu Widagdo (Jurnal Audience: Jurnal Ilmu Komunikasi, 2026)
This study analyzes the effectiveness of the implementation of Community Information Group (KIM) in community empowerment in Palembang city with a focus on visualizing public messages. Different from previous research that focused more on institutional sustainability, technology access, and digital services, this study examines how message visualization links the dissemination of public information with community understanding, participation, and action. The study uses the perspectives of development communication, participatory communication, diffusion of innovation, and visual communication to analyze the process of processing, simplifying, visualizing, and disseminating government information by KIM. The study used a descriptive qualitative approach with primary data from KIM and community managers and secondary data in the form of institutional documents, literature, and information on KIM's activities. The results showed that the effectiveness of KIM is multilevel. At the dissemination level, KIM is relatively effective in delivering digital public service information, antihoak education, MSME promotion, and local programs. However, at the empowerment level, effectiveness is still moderate because increased attention and understanding has not always progressed to behavior change, sustained participation, or broader socio-economic impact. These conditions are influenced by volunteer capacity, quality of visual content, digital literacy, local government support, and institutional follow-up. This study confirms the need to combine message visualization with face-to-face communication, mentoring, institutional networking, and government response. The novelty of the research lies in the placement of KIM as an actor of visual-participatory communication as well as an analytical distinction between the effectiveness of dissemination and empowerment.